Os significados da economia solidária: o caso da Rede Cearense de Socioeconomia Solidária - Dantas, Deuzimar da Silva (2013)
This research focuses on the field of solidarity economy. It seeks to comprehend the meanings this social phenomenon incorporates within the context of Rede Cearense de Socioeconomia Solidária (RCSES). RCSES is one of the institutions that represent the named solidarity economic businesses in Ceará. The objective was mainly to understand their political potential of creating new meanings and practices which are capable of confronting dominant notions of politics, economy and sociability, as well as the various forms of exclusion and discrimination which are within social relationships in Brazil. In this sense, the methodological approach used is qualitative and understanding because the research looks for noticing the meaning of the social actions that are part of the solidarity economy movement in Ceará. The work tries to understand how the movement is organized taking into account the actions of people who belong to RCSES. First, it is possible to say RCSES creates “the politics of meaning” because it has as focus discuss alternatives ways of thinking about material subsistence, and of building new social bond. On the other hand, there are ambiguities and reproduction of discourses and practices in the movement that restrain an effective participation of people in the main decisions about economic and political issues.